2020
DOI: 10.3233/jad-200551
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The Iron Chelator Deferiprone Improves the Phenotype in a Mouse Model of Tauopathy1

Abstract: Background: Abnormally hyperphosphorylated tau is a defining pathological feature of tauopathies, such as Alzheimer’s disease (AD), and accumulating evidence suggests a role for iron in mediating tau pathology that may lead to cognitive decline in these conditions. The metal chelator deferiprone (DFP), which has a high affinity for iron, is currently in clinical trials for AD and Parkinson’s disease. However, the effect of DFP on tau pathology remains underexplored. Objective: We aimed to investigate the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…In animal models of tauopathies, increased iron associated with aging and neurodegeneration has been observed [149]. Indeed, animals with tauopathies treated with the iron chelator deferiprone showed a trend toward improved cognitive function associated with the decrease in brain iron levels and sarkosyl-insoluble tau [150].…”
Section: Ferroptosis In Alzheimer's Diseasementioning
confidence: 99%
“…In animal models of tauopathies, increased iron associated with aging and neurodegeneration has been observed [149]. Indeed, animals with tauopathies treated with the iron chelator deferiprone showed a trend toward improved cognitive function associated with the decrease in brain iron levels and sarkosyl-insoluble tau [150].…”
Section: Ferroptosis In Alzheimer's Diseasementioning
confidence: 99%
“…Therapeutically, iron chelator desferrioxamine has already been conducted a clinical trial in AD in 1991 (Crapper McLachlan et al, 1991). A randomized, multi-center, doubleblind Phase II trial using deferiprone for AD patients (clinical trial NCT03234686) is currently ongoing in Australia (Rao et al, 2020). Moreover, as mentioned above, Se can increase the resistance of cells to ferroptosis.…”
Section: Admentioning
confidence: 99%
“…In addition, based on the structure of DFP with the benzothiazole moiety of ThT, compound 2d (from reference [284]) was developed, and it showed a strong Fe-chelating ability [284]. Moreover, recent animal studies showed that DFP could regulate the Aβ levels and phosphorylation of tau, leading to improved cognitive function in a transgenic mouse model of tauopathy, rTg4510 (Table 3) [285][286][287]. The results of clinical trials (phase II) of DFP are summarized in Table 1 [288].…”
Section: Regulators Of Fe(ii/iii)mentioning
confidence: 99%
“…Moreover, they could affect the aggregation of Fe(III)-Aβ 42 and disassemble preformed Fe(III)-Aβ 42 aggregates [202]. Based on multifunctionality, a few chemical agents, although they have firstly been suggested as Fe(II/III) chelators, have recently been examined for their potentials as therapeutic agents for AD in various animals (Table 3) [280][281][282][285][286][287][292][293][294].…”
Section: Hla20mentioning
confidence: 99%